Political vs Everyday Forms of Governance in Uzbekistan: the Illegal, Immoral and Illegitimate - Urinboyev, Rustamjon; Polese, Abel; Svensson, Mans; Adams, Laura; Kerikmäe, Tanel (Studies of Transition States and Societies, 2018)
Based on extensive ethnographic fieldwork in Uzbekistan, this article looks at the way official state narratives are challenged by silent, unorganised, often unaware gestures of resistance at the bottom of a society. Footing on a framework suggested by Scott’s definition of infrapolitics (2012), we propose to incorporate informal practices in a definition of informality that is more inclusive and better explains the anatomy of a modern state, whose functioning rests on a combination of formal and informal practices. We suggest that this everyday dimension is of particular importance here when trying to understand the governance trajectories, as it allows to look critically, and from a broader perspective, at situations where individual and state perception of events, but also individual and state morality, diverge.By doing this, we propose that governance in transition states and societies may be regarded as a space where formal institutions and citizens (or informal institutions) compete for power and resources and thereby produce informal, alternative ‘legal orders’ and mechanisms that regulate public life in a given area. We will suggest that such a space of informal negotiation is vital in contexts where collective mobilisation and public articulation of social claims is not a preferred, or even available, strategy for citizens.